Quorum sensing molecules in yeast wastewater treatment and their regulation of yeast cell morphology. (October 2022) - Zhang, Quandi; Xiang, Jinhao; Lv, Wenzhou; Liu, Ying; Sun, Jianmin; Wan, Pengfei; Jiang, Li
Abstract: Yeast cells can transform from yeast form into mycelium form under some circumstances, resulting in poor cell settleability and seriously deteriorating the stability of system operation. The feasibility of mediating cell morphology by quorum sensing was carried out in this study. The results showed that the predominant species in the system, Candida tropicalis, could secrete quorum sensing molecules(QSMs) in some media. The supernatant of yeast extract-peptone-dextrose medium(YPD) or yeast filamentation-induced medium(YCBP) after cultivating Candida tropicalis could inhibit mycelial transformation in YCBP, implying that this strain could secrete QSMs. Further, QSMs-(E, E)-farnesol, 2-phenylethanol(2-PE) and a cell filamentation inhibitor 2, 4-di-tert-butylphenol(2, 4-di-TBP) were detected in YPD supernatant and a lab-scale SBR system in treating oil-containing wastewater. 2-PE and 2, 4-di-TBP were detected in the supernatant of YCBP, indicating that the kinds of QSMs depended on substrate components. Finally, the detected compounds were added to a filamentation-induced media to investigate the optimal supplement time to antagonize cell morphological transformation. The results showed that the addition of (E, E)-farnesol, 2-PE, or 2, 4-di-TBP could inhibit the morphological transformation from yeast form into mycelium form within the first 3 h of induction, with the maximum inhibition rates of mycelia number and length of 78.1 ± 3.5 % and 59.4 ± 12.7 % for 300 μM (E, E)-farnesol, respectively. For 100 μM 2, 4-di-TBP, the highest mycelia number and length inhibition rates were achieved at 98.5 ± 2.3 % and 86.8 ± 5 %. Supplements of QSMs or filamentation inhibitors to the system are expected to inhibit yeast filamentation and establish an efficient and stable yeast wastewater treatment system. Graphical abstract: Unlabelled Image Highlights: Spent YPD or YCBP could inhibit cell filamentation of C. tropicalis in YCBP media. QSMs-(E, E)-farnesol and 2-PE and a filamentation inhibitor 2, 4-di-TBP were detected. The concentration of QSMs and 2, 4-di-TBP in the yeast-SBR system decreased gradually. QSMs or filamentation inhibitor prevent mycelia formation within the first 3 h of induction. Enhancement of QSMs in system may be a promising cell filamentation inhabitation way.